PENGELOLAAN PEMBELAJARAN ILMU PENGETAHUAN ALAM DI SDMELALUI MEDIA SEDERHANA - Ulung Maryani (Manajer Pendididikan, 2016)
The benefit kind of the learning sources is positive step has been do to improve the quality of Education in the country. This research is classroom action research in two cycles. Activities research in State Elementary School 04 Kepahiang. Based on the observation during of teaching throught the simple media there are concluded: (a) The teacher to convey the material with easy, (b) The student was good responding in process of learning so make appear to learn of science, (c) The purpose of learning achieved. The result of this research showed that the learning of science by using the simple media could improve the studet result of study.Keywords: learning of science, simple media